Influence Deep Learning Approach Framework Merdeka Curriculum towards Realization of Character Education Students at Amanah Nusantara High School - Andi Alviadi Nur Risal; Sriwahyuni Sriwahyuni; Hasanudin Kasim; Sujarwo Sujarwo; Vivit Rosmayanti; Akhiruddin Akhiruddin (Jurnal Studi Guru dan Pembelajaran, 2025)
This study aims to analyze the influence of implementing a deep learning approach within the Merdeka Curriculum framework on the character development of students at Amanah Nusantara High School. The urgency of this research arises from the growing national demand for educational practices that not only strengthen students’ cognitive mastery but also cultivate character values aligned with the Profile of Pancasila Students an area where empirical evidence remains limited, particularly in digital era learning contexts. This study employs a mixed-methods design using a one-group pretest–posttest model. The research participants consist of 29 eleventh-grade students and two Sociology teachers. Quantitative data were collected through a character education questionnaire encompassing responsibility, honesty, care, social awareness, and work ethic, while qualitative data were obtained through in-depth interviews and observations of classroom activities. Descriptive analysis indicates an improvement in the mean character education score from 72.3 (SD = 8.9) in the pretest to 78.9 (SD = 7.4) in the posttest. The Shapiro–Wilk test confirmed normal data distribution (p > 0.05), and a paired-samples t-test showed a significant increase, t(28) = 4.12, p = 0.0003, with a medium-to-large effect size (Cohen’s d = 0.76). Qualitative findings further reveal that the deep learning approach enhances student participation, moral value reflection, and collaborative work, especially during activity-based learning. However, several challenges emerged, including time limitations and the absence of comprehensive character assessment instruments. Overall, the findings confirm that the deep learning approach is effective in cultivating students’ character through reflective, collaborative, and project-based activities aligned with the principles of the Merdeka Curriculum and the Pancasila Student Profile. The study highlights an urgent need for systematic teacher training and the development of character assessment frameworks to support sustainable deep learning practices in Indonesian schools.